Conceptual Metaphor Theory and Translation: A Cognitive Linguistic Analysis of English FEAR Metaphors and Metonymies into Arabic. - Hammas, Wedyan (2021)
One of the fastest-growing developments in Metaphor in Translation Studies lies in the critical applications of Cognitive Linguistics, namely Lakoff and Johnson’s (1980) Conceptual Metaphor Theory (henceforth CMT). From a cognitive linguistic perspective, metaphor and metonymy in Translation Studies are characterised as cognitive linguistic shifts of concepts, especially those where there is an association between space and another domain. This thesis examines the way in which conceptualisation processes play a fundamental role in supporting the translation process of the linguistic manifestations reasoned by an emotion concept from English into Arabic. The thesis is based on existing assumptions about metaphor translation within CMT, and, as such, is expected to go beyond established studies and complement existing ones by also investigating the translation of metonymy as a significant cognitive operation. This investigation highlights theoretical issues and arguments related to the translation of metaphor and metonymy at the level of the cognitive dimension involved. It argues that metaphor and metonymy with patterns of interaction underlying an emotion concept and integrated with image-schematic representations can provide valuable insights into the analysis of translation procedures. This thesis follows a corpus-based approach. It combines qualitative and quantitative methods to investigate the translation of metaphors and metonymies in the context of a specialised corpus extracted from three English popular novels and their Arabic translations. The major conclusions of this study highlight the significant contribution of the conceptual synergy between metaphor and metonymy in CMT in translation. This includes a set of fourteen procedures contained in nine major categories that translators use to handle metaphors and metonymies, with an emphasis on the challenging demands that source domains make upon translators. A key finding of this thesis is that the interactive imageries resulting from metaphor and culture (as well as the latter with metonymy within emotions) likely exert an influence on their treatment in translation. This thesis also demonstrates how the interplay between image-schemas and rich images, and their relationship with culture, can be crucial factors in determining translation decisions.